Fertility Statusof the Koto TibunReservoir, Kampar Regency, RiauBased on NygaardIndex - Nainggolan, Dorma Abigail; HSimarmata, Asmika; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractNygaardindex is an index which can be used to determine the trophic status of waters, based on phytoplankton composition. To understand the trophic status of the Koto Tibun Reservoir, a research was conducted on February-March 2018. There were three sampling station, namely station 1 (riverin zone), station 2 (transition zone) and station 3 (lacustrin zone). Samplings were conducted 3 times, once/week. Water quality parameters measured were temperature, pH, free CO2, nitrate and phosphate. Results shown that the Nygaard Index values ranged from 2,4-3. The water quality parameters were as follows : temperature : 25.3-25.60C, transparency 75-79 cm, pH 5, free CO2 : 18.64-19.44 mg/L. Based on the Nygaard Index value, the Koto Tibun reservoir can be categorized as mesotrophic to eutrophic. Keyword :Phytoplankton, Koto Tibun Dam, Water Quality Parameters, Mesotrophic